A new species of Oiovelia (Heteroptera: Gerromorpha: Veliidae) from Mesoamerica, with an identification key to the genus - Floriano, Carla Fernanda Burguez; Rodrigues, Higor D. D. (Zootaxa, 2016)
Oiovelia johnpolhemi sp. nov. is described and illustrated based on macropterous specimens collected in Mexico and Belize. This species is the tenth of the genus, and represents its first record outside South America. An updated identification key and distribution maps of all species of Oiovelia are presented. Finally, photographs of the macropterous form of O. spumicola Spangler are presented for the first time.